IMPROVING SPEAKING SKILL THROUGH PROBLEM-BASED LEARNING (A quasi experimental research on the fourth semester students of English Department at IAIN Ponorogo) - Dedi Hasnawan (Universitas Majalengka, 2018)
This study is aimed to find the effect of using Problem-Based Learning on Speaking Ability of the fourth semester students of English department at state institute of Islamic Studies (IAIN), Ponorogo. The study was an experimental research. It can be interpreted as the way to find the relation of cause-effect (causal relation) between two factors or to find the effects of a treatment. There were two classes: experiment class and control class. This research was conducted based on quasi-experimental design because the sample of the study (control and experimental class) is not randomly chosen but from the existing class. Based on the research conducted, the calculation of t-test in post-test scores shows the result of the research that experimental group got higher score than the control group score. In other word, the t obtain (2.674) is higher than t critical (1.879) meaning that the null hypothesis is rejected. It means that there is significant difference of means between experimental group that was given Problem-Based Learning treatment and control groups that was not. In other words, having been treated by Problem-Based Learning, students have a significant improvement of their speaking skill. Problem-Based Learning has some advantages. Problem-Based Learning can facilitate the students to improve their speaking ability through problem solving activity. Problem-Based Learning also gives the students the opportunity to explore their own knowledge. It also gives the students the chance to improve their critical thinking, creativity, and imagination during the problem solving activity